The Cambridge history of Southeast Asia - Tarling, Nicholas (Cambridge University Press, 1999)
The establishment of the colonial régimes. Political structures in the nineteenth and early twentieth centuries. Imternational commerce, the State and society: economic and social change. Religion and anti-colonial movements. Nationalism and modernist reform.